Activity of neurochemically heterogeneous dopaminergic neurons in the substantia nigra during spontaneous and driven changes in brain state. - Brown, M; Henny, P; Bolam, J; Magill, P (2009)
Dopaminergic neurons of the substantia nigra (SN) and ventral tegmental area (VTA) are collectively implicated in motor- and reward-related behaviors. However, dopaminergic SN and VTA neurons differ on several functional levels, and dopaminergic SN neurons themselves vary in their intrinsic electrical properties, neurochemical characteristics and connections. This heterogeneity is not only important for normal function; calbindin (CB) expression by some dopaminergic SN neurons has been linked with their increased survival in Parkinson's disease. To test whether the activity of CB-negative and CB-positive dopaminergic SN neurons differs during distinct spontaneous and driven brain states, we recorded single units in anesthetized rats before, during and after aversive somatosensory stimuli. Recorded neurons were juxtacellularly labeled, confirmed to be dopaminergic, and tested for CB immunoreactivity. During cortical slow-wave activity, the firing of most dopaminergic neurons was slow and regular/irregular and unrelated to cortical slow oscillations. During spontaneous cortical activation, dopaminergic SN neurons fired in a more regular manner, with fewer bursts, but did not change their firing rate. Regardless of brain state, CB-negative dopaminergic neurons fired significantly faster than CB-positive dopaminergic neurons. This difference in firing rate was not mirrored by different firing patterns. Most CB-negative and CB-positive dopaminergic neurons did not respond to the aversive stimuli; of those that did respond, most were inhibited. We conclude that CB-negative and CB-positive dopaminergic neurons exhibit different activities in vivo. Furthermore, the firing of dopaminergic SN neurons is brain state-dependent, and, unlike dopaminergic VTA neurons, they are not commonly recruited or inhibited by aversive stimuli.